Nineteenth-century religion, literature and society.
1 online resource
Keywords: Part of a four-volume set, this third volume looks at 'religious feeling' as an important and distinct category for understanding the ways in which religion is embodied and expressed in culture. The complete four-volume historical resource provides new opportunities for investigating the relationship between religion, literature and society in Britain and its imperial territories by making accessible a diverse selection of harder-to-find primary sources. These include religious fiction, poetry, essays, memoirs, sermons, travel writing, religious ephemera, unpublished notebooks and pamphlet literature. Spanning the long nineteenth century (c.1789-1914), the resource departs from older models of 'the Victorian crisis of faith' in order to open up new ways of conceptualising religion.